Synthetic MRI study of brain volume and subcortical myelin in various Parkinson’s disease motor subtypes - Dongliang Cheng; Junyan Wen; Nan Ding; Zhenpeng Duan; Biqing Lin; Yunjun Yang; Yaozhong Wu; Hang Wang; Jincheng Ma; Jialu Zhang; Zhifeng Xu; Hai Zhao; et al. (npj Parkinson's Disease)
Abstract Alterations in brain volume and subcortical myelin content (MyC) between tremor-dominant (TD) and postural instability and gait difficulty (PIGD) subtypes of Parkinson’s (PD) disease remain unclear. This study investigated whole-brain volume and subcortical myelin content differences among PD motor subtypes using synthetic MRI. Ninety-two PD patients (39 TD and 53 PIGD) and 39 healthy controls were included. ANCOVA identified that PD patients exhibited reduced gray matter, white matter, and MyC, with no distinct atrophy patterns between TD and PIGD. Most subcortical nuclei showed decreased myelin, while PIGD presented more extensive alterations and increased bilateral caudate myelin; TD exhibited asymmetric thalamic myelin changes, with lateralized increases and decreases. Significant MyC differences in the left caudate and right GPi were observed between TD and PIGD. Synthetic MRI-derived parameters provide insights into whole-brain atrophy patterns and dynamic myelin changes in PD, contributing to a deeper understanding of PD subtypes.